PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mike Mega Rahayu; Rini Fatmala (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2020)
This study aims to determine the effect of liquidity and profitability on stock prices in food and beverage companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2018 period. This research uses quantitative methods. The type of data in this study is secondary data. The research population is food and beverage companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2018 period using the purposive sampling method. Where the samples used were 8 companies from 26 companies so that the total data processed was 32 samples.     This study uses multiple linear regression analysis with the IBM SPSS Statistics 20 program. The results of research on CR and ROE on Stock Prices obtained a t value of 2.681 indicating that the correlation or relationship between the independent variable and the dependent variable is sufficient and (t test) of 2.681 indicates that The stock price is influenced by 26.8% by CR and ROE while the f test is obtained at 3,913 showing that the relationship between the independent variables and the dependent variable is sufficient and (f test) of 3,913 shows that the share price is influenced by 39.1%, the rest is influenced by other factors not researched like ROI. The t test results show that partially CR and ROE have a significant effect on stock prices. Meanwhile, the results of the F test show that CR and ROE simultaneously have a significant effect on share prices in food and beverage companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2018 period.